Supports materialization of Pd based catalysts for NOx removal by hydrogen assisted selective catalytic reduction in the presence of oxygen - Patel V.K.; Sharma S. (My University, 2025)
The Pt and Pd based bimetallic catalyst are developed to address the NOx reduction activity. For this, a series of supports containing three different amounts of CeO2−MgO (9 : 1, 3 : 1, and 3 : 2) are prepared by the co-precipitation method, followed by impregnation of Pd metal precursors. The physicochemical properties of the catalytic system are investigated using various techniques such as Brunauer-Emmett-Teller (BET), X-ray Diffraction (XRD), X-ray photoelectron spectroscopy, Transmission Electron Microscopy (TEM), Raman spectroscopy, and H2-TPR. Among all, Pd/CeO2−MgO (3 : 1) gave the best NOx reduction activity. Furthermore, the effects of hydrogen concentration (0.2–0.8 vol %) on NOx reduction were tested. It was found that 0.8 vol % of H2 shows the highest NOx conversion. Subsequently, the successive impregnation of Pt metal over Pd based catalyst enhanced the catalytic properties. The bimetallic Pt−Pd/CeO2−MgO (3 : 1) catalyst showed an 89 % NOx reduction with about 97 % N2 selectivity in broad temperature windows (100–300 °C). © 2020 Wiley-VCH GmbH